Community Health Workers and Pandemic Preparedness: Current and Prospective Roles - Boyce, Matthew R.; Katz, Rebecca (Frontiers in Public Health, 2019)
Despite the importance of community health workers (CHWs) to health systems in resource-constrained environments, relatively little has been written about their contributions to pandemic preparedness. In this perspective piece, we draw from the response to the 2014 Ebola and 2015 Zika epidemics to review examples whereby CHWs contributed to health security and pandemic preparedness. CHWs promoted pandemic preparedness prior to the epidemics by increasing the access to health services and products within communities, communicating health concepts in a culturally appropriate fashion, and reducing the burdens felt by formal healthcare systems. During the epidemics, CHWs promoted pandemic preparedness by acting as community-level educators and mobilizers, contributing to surveillance systems, and filling health service gaps. Acknowledging the success CHWs have had in these roles and in previous interventions, we propose that the cadre may be better engaged in pandemic preparedness in the future. Some practical strategies for achieving this include training and using CHWs to communicate One Health information to at-risk communities prior to outbreaks, pooling them into a reserve health corps to be used during public health emergencies, and formalizing agreements and strategies to promote the early engagement of CHWs in response actions. Recognizing that CHWs already play a role in pandemic preparedness, we feel that expanding the roles and responsibilities of CHWs represents a practical means of improving pandemic and community-level resilience.